Vaccinia virus-host cell interactions at the metabolic interface - Pant, Anil (Kansas State University, 2021)
Metabolism is a fundamental cellular process. Because viruses lack their own metabolic capability, they must actively interact with and usurp host metabolic machinery for efficient replication. Vaccinia virus (VACV) is the prototypic member of poxviridae family and it is widely used as a model system to study pathogen-host interactions. Like all viruses, VACV relies on the host for the supply of nutrients and energy. However, the viral and the host factors that interact at this crucial interface during VACV infection are poorly understood. This dissertation aims to study the alteration of host metabolism during VACV infection and identify the host and viral factors that are important for these changes. In the first part of the dissertation, we examine why VACV replication heavily relies on glutamine, a non-essential amino acid. In the absence of glutamine, the replication of VACV is severely impaired. We found that the addition of asparagine, an amino acid that exclusively requires glutamine for its biosynthesis, rescues VACV replication from glutamine depletion. Upon VACV infection in the absence of glutamine, asparagine becomes the least abundant amino acid. While the addition of asparagine did not elevate the tricarboxylic acid (TCA) cycle activities or the nucleotide levels, it did reduce the imbalance of amino acid levels resulting from glutamine deprivation. Accordingly, asparagine rescued VACV replication from glutamine depletion by rescuing the post-replicative mRNA translation. Consistent with this, when we disrupted asparagine metabolism using chemical or genetic approaches VACV replication was suppressed. In all, our data show that the asparagine metabolic pathway is important for VACV replication. The regulation of metabolic pathways is important for virus replication as we found that VACV, upon infection, hijacks cellular machinery to redirect cellular nutrients for efficient viral replication. We found that VACV infection causes profound changes in several aspects of host metabolism such as the homeostasis of amino acids, central carbon, and numerous lipids. We further demonstrated that VACV infection leads to increased levels of TCA cycle intermediates, such as citrate. The virus growth factor (VGF), the VACV homolog of cellular epidermal growth factor (EGF), was responsible for this increase by activating the host EGF receptor (EGFR) pathway. We showed that VACV infection leads to non-canonical STAT3 phosphorylation at serine 727 in a VGF-dependent manner. Interestingly, both EGFR and downstream STAT3 pathways are key host factors that are induced by VACV to increase host TCA intermediate levels for efficient replication. We also demonstrate that VACV infection reduces the levels of long-chain fatty acids and increases the carnitine-conjugated fatty acids that are critical for beta-oxidation. Furthermore, we show that the VGF-mediated EGFR pathway is crucial for the activation of a host enzyme that sits at the crossroads of key cellular biochemical processes, indicating VACV could launch a multifaceted attack to hijack host nutrient resources through VGF. Together, our study enhances the understanding of how VACV repurposes host cell metabolism for efficient replication. We elucidated a metabolic vulnerability of VACV infection and identified key host and viral factors that govern the metabolic dynamics during VACV infection. These findings could lead to the development of novel strategies to manage poxvirus infections and facilitate the development of poxviruses-based tools for protein expression, vaccine vectors, and oncolytic treatment. Moreover, these findings can provide knowledge for understanding fundamental mechanisms of cell metabolism.
Keywords: Vaccinia virus; Poxvirus; Metabolism; Growth factors; STAT3; Asparagine